ALGORITMA ASOSIASI UNTUK MENDAPATKAN POLA MATA KULIAH PILIHAN STIE-GK MUARA BULIAN - Anas, Azwar; Darma, Budi (Jurnal EDik Informatika, 2019)
In this study, the authors used the association algorithm to obtain the pattern of taking courses in the electives of STIE-GK Muara Bulian students. The task of data mining is to produce all the rules of association in a transactional table, which has a support value of more than the minimum support. The rule must also have support that is greater than confidence. As for testing the algorithm, the author uses Orange data mining software. The final result of this study is a description of the pattern of taking elective courses that most often occur simultaneously. Based on the discussion in this study, the value of support and confidence with the 2-itemet reference that has the highest value is a combination of Marketing and SKB with 14% support and 18% confidence. Whereas for the 3-itemset reference, there are 4 association rules that meet the minimum support and minimum confidence requirements. It was found that all combinations of the elective courses of Marketing, SKB and HRM had the highest scores, namely 12% support and 85% confidence.Keywords: algorithm, a priori, data mining, courses.